Review: Medical Waste Management for Covid19 - Hendri Sutrisno; Fitriana Meilasari (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: Medical waste generation during the Covid19 pandemic increased by around 30%. Sources of medical waste generation are health care activities. If medical waste is not appropriately managed, it can pollute the environment and disturb health. The purpose of the review is to identify the potential of medical waste in health-care facilities in Indonesia when the Covid19 pandemic and to review medical waste management in Indonesia. The analysis uses a systematic literature review. Discussion: The potential of medical waste during the Covid19 epidemic is infectious waste (PPE wastes), sharps waste (syringes), chemical waste (expired medicines), and pharmaceutical waste (the used alcohol bottles when rapid tests). The hazardous waste management system refers to Government Regulation No. 101 year 2014 about Management of Hazardous and Toxic Waste and and Regulation of Minister of Environment and Forestry of Republic Indonesia No. P.56/MenlhkSetjen/2015 about Procedures and Technical Requirements for Waste Management Hazardous and Toxic From the Health Service Facilities. Infectious waste, sharps waste, chemical waste, and pharmaceutical waste are destroyed with incinerators. Syringe residues were damaged with a needle shredder. Residue and incineration ashes are processed using solidification. If the heavy metal content under the quality standards, then the waste can be landfill. Conclusion: The potential of medical waste during the Covid19 pandemic is infectious waste, sharps waste, chemical waste, and pharmaceutical waste. Medical waste generated must be appropriately managed. Proper medical waste management can prevent environmental pollution and the spread of disease. One of the processing of potential medical waste is incineration. The incineration system produces residue and ash waste that must further be handled so that it does not pollute the environment and disturb health.